Coordination Chemistry of the Benzaldehyde(1R)(-)Fenchone Azine and Derivatives Fench=NN=C(H)C6H4X (X = H, Cl, Br, OMe or NO2 in the Meta or Para Positions) with Palladium - Mustaffa Ahmad (Tanjong Malim, 2009)
Coordination Chemistry of the Benzaldehyde(1R)(-)Fenchone Azine and Derivatives Fench=NN=C(H)C6H4X (X = H, Cl, Br, OMe or NO2 in the Meta or Para Positions) with Palladium by Mustaffa Ahmad